2017
DOI: 10.1007/978-3-319-60131-1_30
|View full text |Cite
|
Sign up to set email alerts
|

Recruiting from the Network: Discovering Twitter Users Who Can Help Combat Zika Epidemics

Abstract: Tropical diseases like Chikungunya and Zika have come to prominence in recent years as the cause of serious, long-lasting, populationwide health problems. In large countries like Brasil, traditional disease prevention programs led by health authorities have not been particularly effective. We explore the hypothesis that monitoring and analysis of social media content streams may effectively complement such efforts. Specifically, we aim to identify selected members of the public who are likely to be sensitive t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
1

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 14 publications
2
10
0
Order By: Relevance
“…This means that for the majority of users the number of COVID-19 posts follows the increasing of the number of total posts. Missier et al [48] showed that social media analytics can be used to pinpoint individuals who are actively contributing to social discourse on the specific topic of the Zika virus and its consequences, and are thus likely to be sensitive to health promotion campaigns, by focusing on Twitter content related to the Zika virus and its effect on people. For our case, also, we find some users who can be qualified as COVID-19 publish engine despite that their accounts are for persons.…”
Section: Facebook Users Covid-19 Related Behaviourmentioning
confidence: 99%
“…This means that for the majority of users the number of COVID-19 posts follows the increasing of the number of total posts. Missier et al [48] showed that social media analytics can be used to pinpoint individuals who are actively contributing to social discourse on the specific topic of the Zika virus and its consequences, and are thus likely to be sensitive to health promotion campaigns, by focusing on Twitter content related to the Zika virus and its effect on people. For our case, also, we find some users who can be qualified as COVID-19 publish engine despite that their accounts are for persons.…”
Section: Facebook Users Covid-19 Related Behaviourmentioning
confidence: 99%
“…This means that for the majority of users the number of COVID-19 posts follows the increasing of the number of total posts. Missier et al (2017) showed that social media analytics can be used to pinpoint individuals who are actively contributing to social discourse on the specific topic of the Zika virus and its consequences, and are thus likely to be sensitive to health promotion campaigns, by focusing on Twitter content related to the Zika virus and its effect on people. For our case, also, we find some users who can be qualified as COVID-19 publish engine despite that their accounts are for persons.…”
Section: Facebook Users Covid-19 Related Behaviourmentioning
confidence: 99%
“…Help from community activists is badly needed to supplement the scarce public resources deployed on the ground, and efforts have been recorded to document how technology can be brought to bear for this [3,29]. Our own work in this setting has so far focused on identifying relevant content on Twitter that may point health authorities directly to mosquito breeding sites [31], as well as to users who have shown interest in those topics, i.e., by posting relevant content on Twitter [20]. In this work we generalise such efforts, with an aim to develop techniques for the semi-automatic detection of online activists on Twitter.…”
Section: Introductionmentioning
confidence: 99%